Guidelines for the Management of Upper Respiratory Tract Infections - A. Brink (South African Family Practice)
Introduction: Inappropriate use of antibiotics for upper respiratory tract infections (URTIs), many of which are viral, adds to the burden of antibiotic resistance. Antibiotic resistance is increasing in Streptococcus pneumoniae, responsible for most cases of acute otitis media (AOM) and acute bacterial sinusitis (ABS).